1996
DOI: 10.1111/j.1745-6592.1996.tb00131.x
|View full text |Cite
|
Sign up to set email alerts
|

The Rehabilitation of Monitoring Wells Clogged by Calcite Precipitation and Drilling Mud

Abstract: Based on aquifer performance tests, 13 out of 15 wells situated at the Mixed Waste Disposal (MWD) area located at the Savannah River site. South Carolina, exhibited high skin factors and low well efficiencies indicative of severely damaged wells. The use of damaged wells in aquifer testing can lead to inaccurate determinations of aquifer properties, and such wells are unusable in future remediation programs. Moreover, damaged wells can go dry during purging, thus compromising sample collection. Pump tests, che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…5) can be used to interpret the conductivity around the wellbore (e.g., Kroening et al 1996). A positive skin factor indicates additional flow resistance near the wellbore, e.g., caused by drilling fluid additives invaded into the aquifer or accumulated fines.…”
Section: Head Losses In the Aquifermentioning
confidence: 99%
“…5) can be used to interpret the conductivity around the wellbore (e.g., Kroening et al 1996). A positive skin factor indicates additional flow resistance near the wellbore, e.g., caused by drilling fluid additives invaded into the aquifer or accumulated fines.…”
Section: Head Losses In the Aquifermentioning
confidence: 99%
“…[34] It is well known that injected air removes or ''strips'' CO 2 from aqueous solutions and causes the pH to increase even at the field scale; as a result, carbonates precipitate from the pore water [e.g., Florida Department of Environmental Protection, 2003;URS, 2003;Miller and Roote, 2001;Kroening et al, 1996; U.S. Environmental Protection Agency, 1995; U.S. Department of Energy, 1995]. As noted in section 2.3, the tap water used in our experiment was derived from groundwater and is supersaturated with CO 2 .…”
Section: Chemical Processes: Experimental Analysis Of the Cemented Agmentioning
confidence: 99%
“…Clogging phenomena were observed in other contexts. Kroening et al (1996) showed for a mixed waste disposal area located at the Savanah River Site, South California, that the main reason for clogging in monitoring-wells was calcite precipitation. Zengguang et al (2011) demonstrated from hydrodynamical simulations in a radial collecting system of a tailing dam that clogging occurred preferentially around the vertical shafts.…”
Section: Recommendationsmentioning
confidence: 98%